Metastatic Malignant Melanoma Mimicking Benign Breast Cysts - Lund-Iversen, Marius (Hindawi Publishing Corporation, 2011)
Benign cysts are one of the most common mass-occupying lesions of the breast and are often investigated with triple diagnostic trial (clinical examination, radiology, and cytology). Malignant melanoma is one of medicine's imitators, and metastatic disease can mimic cysts. Thorough investigation of any breast mass is essential to clarify its nature.